The LepR-mediated leptin transport across brain barriers controls food reward - Alessandro Di Spiezio; Elvira Sonia Sandin; Riccardo Dore; Helge Müller-Fielitz; Steffen E. Storck; Mareike Bernau; Walter Mier; Henrik Oster; Olaf Jöhren; Claus U. Pietrzik; Hendrik Lehnert; Markus Schwaninger (Elsevier, 2018)
Objective: Leptin is a key hormone in the control of appetite and body weight. Predominantly produced by white adipose tissue, it acts on the brain to inhibit homeostatic feeding and food reward. Leptin has free access to circumventricular organs, such as the median eminence, but entry into other brain centers is restricted by the blood-brain and blood-CSF barriers. So far, it is unknown for which of its central effects leptin has to penetrate brain barriers. In addition, the mechanisms mediating the transport across barriers are unclear although high expression in brain barriers suggests an important role of the leptin receptor (LepR). Methods: We selectively deleted LepR in brain endothelial and epithelial cells of mice (LepRbeKO). The expression of LepR in fenestrated vessels of the periphery and the median eminence as well as in tanycytes was not affected. Results: Perfusion studies showed that leptin uptake by the brain depended on LepR in brain barriers. When being fed with a rewarding high-fat diet LepRbeKO mice gained more body weight than controls. The aggravated obesity of LepRbeKO mice was due to hyperphagia and a higher sensitivity to food reward. Conclusions: The LepR-mediated transport of leptin across brain barriers in endothelial cells lining microvessels and in epithelial cells of the choroid plexus controls food reward but is apparently not involved in homeostatic control of feeding. Keywords: Leptin, Reward, Blood-brain barrier, LepR, Obesity, Endothelial cells